Hydrodynamic cavitation using vortex diode: an efficient approach for elimination of pathogenic bacteria from water - Jain, Pooja; Bhandari, Vinay M.; Balapure, Kshama; Jena, Jyotsnarani; Ranade, Vivek V.; Killedar, Deepak J. (Journal of Environmental Management, 2019)
The present study successfully demonstrates greener methodology of hydrodynamic cavitation using rotational flows for disinfection of water. Disinfection of two model microbial strains-gram-negative (Escherichia colt) and gram-positive (Staphylococcus aureus) using vortex diode was evaluated. The removal efficacy was quantified for two different cavitation reactors. Practically complete elimination of E. coli was achieved (99%) after 1 h of cavitation at a pressure drop of only 0.5 bar. However, elimination of S. aureus using vortex diode was observed to be lower in comparison to the removal of E. coli and only 60% disinfection could be achieved under similar conditions, which can be subsequently enhanced up to 98% by increasing pressure drop. The results were compared with another cavitating device that employs linear flow for cavitation, orifice. The reactor geometry has significant impact on the disinfection process and orifice was found to require significantly higher pressure drop (10 bar) conditions for disinfection and for eliminating grain-positive bacteria with high efficiency. A plausible mechanism for disinfection was proposed to elucidate the role of cavitation in cell destruction leading to death of cells through the rupture of cell wall, oxidative damage and possible DNA denaturation. Also, a cavitation model using per pass disinfection was developed that can provide meaningful physical description of the disinfection process as against the conventional first order reaction rate model. This study would provide meaningful insight into cavitation process based on hydrodynamic cavitation for the destruction of both gram-negative and gram-positive bacteria from various water sources, including industrial wastewaters.
Keywords: Cavitation; Disinfection; kinetics; pollution; Wastewater treatment

Destroying antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study reports, for the first time, a new and techno-economic strategy for effective removal of antimicrobial resistant bacteria (AMR) and difficult, opportunistic pathogen using cavitation and natural oils/plant extract. A hybrid methodology using natural oils of known health benefits has been discussed in combination with conventional physico-chemical method of hydrodynamic cavitation that not only provides efficient and effective water disinfection, but also eliminates harmful effects of conventional methods such as formation of disinfection by-products apart from reducing cost of treatment. A proof-of concept is demonstrated by achieving exceptionally high rates for practically complete removal of antimicrobial resistant (AMR) and relatively less researched, gram-negative opportunistic pathogen, Pseudomonas aeruginosa and gram-positive methicillin resistant, Staphylococcus aureus using a natural oil-Peppermint oil and two different cavitating reactors employing vortex flow (vortex diode) and linear flow (orifice) for hydrodynamic cavitation. > 99% disinfection could be obtained, typically in less than 10 min, using vortex diode with operating pressure drop of 1 bar and low dose of 0.1% peppermint oil as an additive, depicting very high rates of disinfection. The rate of disinfection can be further increased by using simple aeration which can result in significant lowering of oil dose. The conventional device, orifice requires relatively higher pressure drop of 2 bar and comparatively more time (similar to 20 min) for disinfection. The cost of the disinfection was also found to be significantly lower compared to most conventional processes indicating techno-economic feasibility in employing the developed hybrid method of disinfection for effectively eliminating bacteria including AMR bacteria from water. The developed approach not only highlights importance of going back to nature for not just conventional water disinfection, but also for eliminating hazardous AMR bacteria and may also find utility in many other applications for the removal of antimicrobial bacteria.
Keywords: AMR bacteria; Cavitation; Disinfection; Oil; Water treatment

Novel hybrid cavitation process for enhancing and altering rate of disinfection by use of natural oils derived from plants - Mane, Maya B.; Bhandari, Vinay M.; Balapure, Kshama; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2020)
The present study is an attempt to improvise the hydrodynamic cavitation methodology for effective disinfection of water and also to suggest prototype development for practical application. The enhancement in the disinfection efficiency was evaluated specifically for the effect of pressure, temperature, pH, microbial inoculum size and also on effect of different additives for the two model microbial strains, gram-negative (Escherichia coli) and gram-positive (Staphylococcus aureus). The efficacy of the hydrodynamic cavitation is evaluated for the two types of flows/cavitation devices - linear flow in the case of orifice and vortex flow for vortex diode. The vortex diode requires significantly lower pressures, 50% lower as compared to orifice for the similar extent of disinfection. While the bacterial disinfection at high temperature is known, the usefulness of hydrodynamic cavitation is especially evident at ambient conditions and the process is effective even at very high concentrations of bacteria, not reported so far. The reactor geometry also has significant effect on the disinfection. The present study, for the first time, reports possible use of different natural oils such as castor oil, cinnamon oil, eucalyptus oil and clove oil in conjunction with hydrodynamic cavitation. The nature of oil modifies the cavitation behavior and an order of magnitude enhancement in the cavitation rate was observed for the two oils, eucalyptus and clove oil for a very small concentration of 0.1%. The increased rates of disinfection, of the order of 2-4 folds, using oil can drastically reduce the time of operation and consequently reduce cost of disinfection. A possible mechanism is proposed for the effect of oil and hydrodynamic cavitation in cell destruction through the rupture of cell wall, oxidative damage and possible DNA denaturation. A cavitation model using per pass disinfection was used to correlate the data. The increased efficiency using oils and possible benefits of the developed process, where natural oils can be perceived as biocatalysts, can have significant advantages in practical applications.
Keywords: Antimicrobial; Cavitation; Disinfection; Oil; Wastewater treatment

Improving efficiency for removal of ammoniacal nitrogen from wastewaters using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Ultrasonics Sonochemistry, 2021)
The present study reports significant improvements in the removal of ammoniacal nitrogen from wastewater which is an important problem for many industries such as dyes and pigment, distilleries and fisheries. Pilot plant studies (capacity, 1 m(3)/h) on synthetic wastewater using 4-amino phenol as model nitrogen containing organic compound and two real industrial effluents of high ammoniacal nitrogen content were carried out using hydrodynamic cavitation. Two reactor geometries were evaluated for increased efficiency in removal-orifice and vortex diode. Effect of initial concentration (100-500 mg/L), effect of pressure drop (0.5-5 bar) and nature of cavitating device (linear and vortex flow for cavitation) were evaluated along with effect of salt content, effect of hydrogen peroxide addition and aeration. Initial concentration was found to have significant impact on the extent of removal: similar to 5 g/m(3) removal for initial concentration of 100 mg/L and up to 12 g/m(3) removal at high concentration of 500 mg/L. Interestingly, significant improvement of the order of magnitude (up to 8 times) in removal of ammoniacal nitrogen could be obtained by sparging air or oxygen in hydrodynamic cavitation and a very high removal of above 80% could be achieved. The removal of ammoniacal nitrogen by vortex diode was also found to be effective in the industrial wastewaters and results on two different effluent samples of distillery industry indicated up to 75% removal, though with longer time of treatment compared to that of synthetic wastewater. The developed methodology of hydrodynamic cavitation technology with aeration and vortex diode as a cavitating device was found to be highly effective for improving the efficiency of the conventional cavitation methods and hence can be highly useful in industrial wastewater treatment, specifically for the removal of ammoniacal nitrogen.
Keywords: Amino phenol; Cavitation; Oxidation; pollution; Wastewater treatment

Safe water and technology initiative for water disinfection: application of natural plant derived materials - Mane, Maya B.; Bhandari, Vinay M.; Ranade, Vivek V. (Journal of Water Process Engineering, 2021)
Safe drinking water is the necessity of life. The present study reveals use of natural resources such as plant extracts and natural oils for water disinfection. Differences between oil and water soluble additives were highlighted for plant extracts and insoluble natural oils. A hybrid hydrodynamic cavitation process was quite effective in both the cases and high rates of disinfection were achieved. Studies were reported using oils (ginger, turmeric, lavender, tulsi) and rhizome derived plant extracts such as ginger, turmeric and mango ginger, as additives in process intensification (0.1% v/V). A vortex based cavitation device (vortex diode, nominal capacity 1 m3/h) was used with pressure drop of 1 bar. A high disinfection of 96% and 88% was obtained in 15 min for ginger oil and mango ginger extract respectively as compared to 44% using cavitation alone. Acoustic cavitation gave 94% and 30% disinfection with and without additive-mango ginger extract. The FTIR analyses before and after cavitation, with ginger additive, showed no by-products formation and indicated gingerol as active component in disinfection. The per-pass disinfection values were also higher, up to 5 times than cavitation alone. Hybrid hydrodynamic cavitation using natural plant derived materials can offer a promising technology alternative in water disinfection.
Keywords: Cavitation; Disinfection; Natural oil; Plant extract; Water treatment

Wastewater treatment and process intensification for degradation of solvents using hydrodynamic cavitation - Patil, Pravin B.; Bhandari, Vinay M.; Ranade, Vivek V. (Chemical Engineering and Processing-Process Intensification, 2021)
Industrial wastewater treatment for removal of small concentrations of harmful solvents is pertinent issue in many chemical and pharmaceutical industries. The present work evaluates removal of three common solvents by hydrodynamic cavitation (nominal capacity, 1m(3)/h). Solvent degradation of three solvents viz. octanol, dimethyl formamide and cyclohexanol was studied in the concentration range of 50-200 mg/L and for the pressure drop range of 0.5-5 bar. The vortex based cavitation device (vortex diode) was compared with that of linear flow based device (orifice). Process intensification in the form of aeration and addition oxidizing agent-hydrogen peroxide was also evaluated for synergistic effect. The vortex diode required lower pressure drop and is superior to orifice and process intensification using aeration is most effective. A reduction in TOC to the extent of 74% could be achieved for octanol (200 ppm) using aeration with cavitational yield of 1202x10(-4) mg/J for vortex diode, yield similar to 10 times of orifice. The degradation depends on the nature of solvent and it was revealed that low values of dielectric constant (epsilon<10) favour degradation. The kinetics was evaluated using rate model based on per-pass degradation factor. The process techno-economic feasibility is useful in industrial wastewater treatment.
Keywords: Cavitation; Effluent; Organics removal; Oxidation; pollution

Enhanced degradation of metformin using surface-coated vortex diodes - Dixit, Divya; Thanekar, Pooja; Bhandari, Vinay M. (Chemical engineering and processing-process intensification, 2023)
The present work successfully demonstrates, for the first time, complete degradation of metformin using newer surface-coated vortex diode (SCVD) with copper and nickel coating to provide catalytic activity in the conventional hydrodynamic cavitation (HC) for significantly enhanced degradation efficiency. The SCVDs have dual functionality and the efficacy of catalytic cavitation reactors get enhanced using process intensifications of the type H2O2 addition, pH modification, and combined approach of HC+ pH+ H2O2 apart from the advantage of low pressure drop for the vortex flow based cavitation in vortex diode (Delta P of 1 bar). Complete, 100%, degradation of metformin (MTF) was achieved within 5 min with integration of optimized H2O2 dose and exceptionally high synergistic index value over 300, indicating extraordinary synergy for both Cu and Ni-SCVD. Acidic condition promote degradation and a complete degradation with a high 43-48% mineralization was observed using HC+ pH 4+ (1:200) H2O2 with less intermediates formation. The SCVDs reveal remarkable enhancement of similar to 9800% in per-pass degradation and 1400-3400% in cavitational yield as compared to conventional cavitation process under similar conditions. The newer SCVDs with catalytic activity can provide more cost-effective solutions for industrial and real-life applications.
Keywords: Cavitation; Oxidation; pollution; Technology; Wastewater treatment